An integrated system for the complete segmentation of the common carotid artery bifurcation in ultrasound images - Loizou, Christos P.; Pantziaris, Marios (My University, 2015)
The complete segmentation of the common carotid artery (CCA) bifurcation in ultrasound images is important for the evaluation of atherosclerosis disease and the quantification of the risk of stroke. The current research work further evaluates and validates a semi-automated (SA) snake’s based segmentation system suitable for the complete segmentation of the CCA bifurcation in two-dimensional (2D) ultrasound images. The proposed system semi-automatically estimates the intima-media thickness (IMT), the atherosclerotic carotid plaque borders and dimensions, the internal carotid artery (ICA) origin’s stenosis, the carotid diameter (D), as well as other geometric measurements of the atherosclerotic carotid plaque. The system was evaluated on 300 2D longitudinal ultrasound images of the CCA bifurcation with manual (M) segmentations available from a neurovascular expert. No statistical significant differences between all M and SA IMT, plaque and D segmentation measurements were found. In a future study, texture features extracted from the intima-media complex (IMC) may be used to separate subjects in high and low risk groups, which may develop a stroke. However, a larger scale study is required for evaluating the system before its application in the real clinical practice.
Keywords: Intima-media thickness; Lumen carotid diameter; Carotid plaque; Carotid artery segmentation; Ultrasound imaging